Method for preparing biomass briquette fuel from municipal solid waste

Through technical means such as humidity adjustment, high-temperature physical modification, gas phase activation, combustion aid additive and multi-stage pressing molding, the problems of low separation accuracy, insufficient fuel calorific value and density, and poor storage stability in urban domestic waste treatment have been solved, and efficient resource utilization and environmental protection performance have been improved.

CN119799384APending Publication Date: 2025-04-11HUANENG JIAXIANG POWER GENERATION CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510086763.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing urban domestic waste treatment technology has problems such as low sorting accuracy, insufficient fuel calorific value and density, and poor storage stability, which limits the efficiency and environmental protection performance of waste resource utilization.

Method used

Through technical solutions combining humidity adjustment, high-temperature physical modification, gas phase activation, combustion aid additive and multi-stage press molding, the garbage forming process is optimized, the fuel density and heat value are improved, and storage stability is improved through surface strengthening treatment.

Benefits of technology

It significantly improves the efficiency of waste resource utilization, improves the combustion performance and storage stability of biomass fuel, improves environmental protection performance, and extends the storage life of fuel blocks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799384A_ABST
    Figure CN119799384A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing biomass briquette fuel from municipal solid waste, which comprises the following steps: separating large-size or irregular impurities including plastics, metals and glass from the municipal solid waste in a mode of combining a drum screen with winnowing equipment, adjusting the humidity of the waste by using low-temperature steam, and drying to obtain the biomass briquette fuel. And the water content of the garbage is uniformly adjusted to 25%-35%, so that the efficiency and the consistency of the subsequent processing technology are optimized. Therefore, the activity of carbon-based substances in materials is further improved through gas-phase activation, the ash content is reduced, the high-density fuel block is prepared through a multi-stage compression molding technology, finally, the surface is strengthened through vegetable wax and a nanometer aluminum oxide coating, the damp-proof performance and the oxidation resistance of the fuel block are improved, and the storage life is prolonged in combination with vacuum packaging. According to the technical scheme, the problems of low sorting precision, insufficient fuel calorific value and density and poor storage stability in the background technology are effectively solved, and the garbage resource utilization efficiency and the industrial application value of the biomass fuel are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fuel production, and in particular to a method for producing biomass shaped fuel from urban domestic waste. Background Art

[0002] At present, the resource-based treatment technologies for urban domestic waste mainly include mechanical sorting, incineration, pyrolysis and simple crushing and molding processes. These technologies can convert part of the waste into combustibles or energy, such as biomass fuel blocks, which can be used in industrial boilers or residential heating, and have a certain resource utilization effect;

[0003] However, the existing technology has obvious shortcomings. The mechanical sorting accuracy is low, and it is impossible to efficiently remove impurities such as metals and glass, resulting in a decrease in fuel quality; harmful gases are easily produced during incineration and pyrolysis, which puts great pressure on environmental protection; the fuel molding process lacks modification treatment and optimization of combustion aids, resulting in low calorific value, poor combustion performance and insufficient storage stability of the finished product, which limits its wide application. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0005] To this end, the purpose of the present invention is to propose a method for producing biomass molded fuel from urban domestic waste. Through a technical solution combining humidity regulation, high-temperature modification, gas phase activation, combustion aid addition and multi-stage pressing and molding, the problems of low sorting accuracy, insufficient fuel calorific value and density in the existing waste treatment process are solved, the combustion performance and storage stability of the fuel blocks are improved, thereby improving the waste resource utilization efficiency and environmental protection performance.

[0006] To achieve the above object, the present invention proposes a method for producing biomass briquette fuel from urban domestic waste, comprising the following steps:

[0007] S1: Humidity regulation and pretreatment

[0008] The municipal solid waste is separated by a drum screen combined with an air separation device to remove large or irregular impurities, including plastic, metal and glass. Low-temperature steam is used to adjust the humidity of the waste to a uniform moisture content of 25%-35% to optimize the efficiency and consistency of subsequent processing technology;

[0009] S2: High temperature physical modification

[0010] The humidity-adjusted garbage is put into a screw compression device to physically modify the garbage under a temperature of 150-200°C and a high pressure environment to destroy the cross-linking structure of cellulose and lignin, improve the plasticity and uniformity of the material, and the volatile organic matter generated during the treatment process is recovered through a condensation collection device for circulating heating or industrial use;

[0011] S3: Carbon-based activation modification

[0012] The incompletely decomposed part of the material surface is subjected to gas phase activation treatment by an airflow activation device, using a 5%-10% oxygen and nitrogen mixed gas, maintaining a low temperature (80-120°C) and slightly positive pressure (0.1-0.5MPa) environment to generate carbon-based active substances with high combustion performance. The gas-phase activated material has higher combustion efficiency and lower ash content;

[0013] S4: Addition of combustion-supporting components

[0014] Adding a modified combustion aid to the garbage material after gas phase activation treatment, the combustion aid is composed of potassium nitrate, magnesium carbonate and inorganic nanoparticles, wherein potassium nitrate accounts for 60%-70% of the total weight, magnesium carbonate accounts for 20%-30%, and inorganic nanoparticles account for 5%-10%. The combustion aid can improve the ignition performance and combustion stability of the fuel and reduce the generation of combustion ash;

[0015] S5: Gradual pressing

[0016] The material after adding the combustion-supporting component is sent to the graded pressing and molding equipment, and the molding is completed according to the following steps:

[0017] The first stage: low-pressure pre-compression, pressure is 5-8MPa, temperature is 50-80℃;

[0018] The second stage: high pressure molding, with a pressure of 10-15MPa and a temperature of 150-200℃, to increase the density of the fuel block;

[0019] The third stage: cooling and shaping, the pressure is maintained at 8-10MPa, and the temperature drops to room temperature;

[0020] The final density of the fuel block reaches 1.2-1.4g / cm 3 , with high strength and high calorific value characteristics;

[0021] S6: Surface strengthening treatment

[0022] The surface of the fuel block is protected by using a mixed coating technology of plant wax and nano-alumina. The coating thickness is 50-100 nanometers. After coating, the fuel block has excellent moisture resistance and antioxidant capacity, and the storage time can be extended to more than 12 months.

[0023] S7: Testing and Packaging

[0024] The finished fuel blocks are subjected to comprehensive quality inspection. The calorific value must reach 20-22MJ / kg, the compressive strength must reach above 2.5MPa, and the moisture content must not exceed 10%. Qualified fuel blocks are packaged using environmentally friendly and degradable materials, and the packaging is vacuum sealed to extend the storage time.

[0025] The present invention discloses a method for preparing biomass molded fuel from urban domestic waste. Impurities are separated and humidity is adjusted by a drum screen and air separation equipment to make the material uniform and stabilize the moisture content. Subsequently, high-temperature physical modification is used to destroy the cross-linking structure of cellulose and lignin to improve the plasticity of the material. Gas phase activation is used to further improve the activity of carbon-based substances in the material and reduce the ash content. After adding a combustion aid, a high-density fuel block is prepared through a multi-stage pressing and molding technology. Finally, the surface is strengthened by a vegetable wax and a nano-alumina coating to improve the moisture-proof and antioxidant properties of the fuel block, and the storage life is extended by combining vacuum packaging. The technical solution effectively solves the problems of low sorting accuracy, insufficient fuel calorific value and density, and poor storage stability in the background technology, and significantly improves the waste resource utilization efficiency and the industrial application value of biomass fuel.

[0026] Specifically, in the humidity adjustment step, low-temperature steam acts on the garbage surface through multi-point injection, the steam temperature is 50-70°C, and the steam injection time is 5-10 minutes; the humidity adjustment process is equipped with a temperature and humidity sensor to ensure that the moisture content is within the range of 25%-35%, and the injection intensity and time are adjusted in real time to adapt to garbage with different humidity.

[0027] Specifically, in the high-temperature physical modification step, a spiral compression device is used to gradually heat the waste material to 150-200°C, and the heating rate is controlled at 10-20°C / minute to prevent excessive fiber decomposition caused by too fast heating. The compression ratio of the spiral compression device is 3:1, and it is equipped with a high-temperature corrosion-resistant coating to prevent volatile acidic substances from corroding the equipment during the treatment process. The volatile organic matter (such as methane and ethanol) released during the treatment process is recovered through a condensation device and can be used for circulating heating or other industrial uses. The volatile gas recovery rate reaches more than 80%.

[0028] Specifically, in the carbon-based activation modification step:

[0029] The mixing ratio of oxygen and nitrogen in the gas phase activation device is 5%-10% oxygen and 90%-95% nitrogen;

[0030] The activation process lasts for 30-60 minutes, the pressure in the activation environment is controlled at 0.2-0.5MPa, and the gas flow rate is 5-10L / min;

[0031] After activation, the proportion of carbon-based active substances in the material increases by 10%-15%, and the ash content decreases to less than 3%.

[0032] Specifically, the inorganic nanoparticles in the combustion-supporting component are nano-silicon dioxide with a particle size range of 10-50 nanometers. The total addition ratio of the combustion-supporting agent is 5%-8% of the material weight. It is fully mixed with the material through high-frequency vibration mixing technology to ensure the uniform distribution of the combustion-supporting component in the fuel block.

[0033] Specifically, the graded pressing molding equipment is a multi-axis multi-stage pressing machine, and the compression channel in the equipment is designed in sections. The length of the initial pressure channel is 30%-40%, and the length of the high-pressure channel is 50%-60%. A high-temperature and wear-resistant coating is set in the channel to extend the life of the equipment.

[0034] Specifically, in the surface strengthening treatment step:

[0035] The vegetable wax is beeswax, palm wax or candelilla wax, the particle size of nano-aluminum oxide is 50-100 nanometers, and the addition ratio is 3%-5% of the total weight of the vegetable wax;

[0036] The coating process adopts spraying + hot melt technology, the coating thickness is controlled at 50-100 nanometers, and the surface smoothness error is controlled at ±5 nanometers;

[0037] The moisture absorption rate of the coated fuel block is reduced by 30%-50%, and the moisture-proof effect can be maintained for more than 12 months.

[0038] Specifically, the calorific value detection in the detection step uses an automatic combustion calorimeter, and the detection error is controlled within ±1%; the compressive strength detection uses a high-precision hydraulic tester, and the detection error is controlled within ±0.1MPa; the moisture content detection uses an infrared moisture analyzer, with a detection range of 0.1%-20%, and a detection error of less than ±0.5%.

[0039] Specifically, the packaging material is prepared by mixing polylactic acid (PLA) and polybutylene succinate (PBAT) in a mass ratio of 70:30, and adding 2%-5% of plant fiber reinforcement material. The packaging material has good mechanical strength and degradability, and the packaging thickness is controlled at 30-50 microns.

[0040] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0042] Figure 1 This is a schematic diagram of the method for producing biomass briquette fuel from urban domestic waste according to the present invention;

[0043] Figure 2 This is a schematic diagram of moisture-proof performance test data of the present invention;

[0044] Figure 3 This is a schematic diagram of the antioxidant capacity test data of the present invention;

[0045] Figure 4 This is a schematic diagram of the long-term storage stability test data of the present invention;

[0046] Figure 5 This is a schematic diagram of fuel performance test data of the present invention;

[0047] Figure 6 This is a schematic diagram of the moisture absorption rate data of the fuel block tested in the present invention;

[0048] Figure 7 This is a schematic diagram of the data of the decrease in calorific value tested in the present invention;

[0049] Figure 8 This is a schematic diagram of the appearance and density change data of the fuel block of the present invention. DETAILED DESCRIPTION

[0050] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limitations of the present invention. On the contrary, embodiments of the present invention include all changes, modifications and equivalents that fall within the spirit and connotation of the appended claims.

[0051] The following describes the method for producing biomass pellet fuel from urban domestic waste in an embodiment of the present invention in conjunction with the accompanying drawings.

[0052] like Figure 1-Figure 8 As shown, the method for making biomass briquette fuel from municipal solid waste according to the embodiment of the present invention may include the following steps:

[0053] S1: Humidity regulation and pretreatment

[0054] The urban domestic waste is separated into larger or irregular impurities, including plastics, metals and glass, by combining a drum screen with an air separation device. The moisture content of the waste is adjusted to 25%-35% using low-temperature steam to optimize the efficiency and consistency of subsequent processing techniques.

[0055] It should be noted that the embodiment described in this invention separates fine ash from urban domestic waste through a drum screen, and removes light plastics, heavy metals and glass impurities through air separation equipment to ensure that the waste entering the humidity adjustment process is mainly composed of organic matter. Low-temperature steam is used to adjust the humidity in a closed environment, and a stirring device is used to evenly distribute the steam to avoid local excessive wetting or drying. During the humidity adjustment process, a temperature and humidity sensor is used to monitor the moisture content of the waste in real time to ensure that the moisture content of the waste after adjustment is stable within the range of 25%-35%.

[0056] S2: High temperature physical modification

[0057] The humidity-adjusted garbage is put into a spiral compression device, where it is physically modified at a temperature of 150-200°C and under high pressure to destroy the cross-linking structure of cellulose and lignin, improve the plasticity and uniformity of the material, and the volatile organic compounds generated during the treatment process are recovered through a condensation collection device for circulating heating or industrial use.

[0058] It should be noted that the garbage after humidity adjustment described in this embodiment is uniformly fed into the spiral compression device, and the material temperature is gradually raised to 150-200°C through segmented heating to ensure uniform heat transfer and avoid local overheating. A compression ratio of 3:1 to 5:1 is applied during the spiral compression process, and the cross-linked structure of cellulose and lignin is destroyed through the synergistic effect of mechanical force and thermal force, which significantly improves the uniformity and plasticity of the material. The volatile organic matter released during the treatment process is separated into liquid and gaseous parts by a condensing device. The liquid part is used for circulating heat, and the gaseous part is used for the energy needs of the auxiliary device.

[0059] S3: Carbon-based activation modification

[0060] The incompletely decomposed parts of the material surface are gas-activated by an airflow activation device, using a 5%-10% oxygen and nitrogen mixed gas to maintain a low temperature (80-120°C) and slightly positive pressure (0.1-0.5MPa) environment to generate carbon-based active substances with high combustion performance. The material after gas-phase activation has higher combustion efficiency and lower ash content.

[0061] It should be noted that the material described in this embodiment is evenly fed into the airflow activation device, and the flow rate and concentration of the mixed gas are accurately controlled by multi-point distributed airflow nozzles to ensure that the surface of the material is fully activated. By setting the reaction time of the gas phase activation to 20-40 minutes and maintaining the temperature at 80-120°C, the unreacted organic components are gradually decomposed, and the number of carbon-based active sites on the surface of the material is increased. An exhaust gas purification system is provided during the activation process, and a small amount of by-products generated during the activation process are recovered or treated, thereby further improving the environmental performance and resource utilization efficiency of the device.

[0062] S4: Addition of combustion-supporting components

[0063] A modified combustion aid is added to the garbage material after gas phase activation treatment. The combustion aid consists of potassium nitrate, magnesium carbonate and inorganic nanoparticles, wherein potassium nitrate accounts for 60%-70% of the total weight, magnesium carbonate accounts for 20%-30%, and inorganic nanoparticles account for 5%-10%. The combustion aid can improve the ignition performance and combustion stability of the fuel and reduce the generation of combustion ash.

[0064] It should be noted that the modified combustion aid described in this embodiment is evenly added to the activated waste material through high-precision quantitative addition equipment to ensure that the combustion aid is fully in contact with the material and dispersed. The potassium nitrate in the combustion aid is treated by a spray drying process to improve its stability, and the magnesium carbonate is made into ultrafine particles by a ball milling process to enhance the combustion reaction efficiency. The inorganic nanoparticles are surface modified to improve the dispersibility and heat resistance of the combustion aid in the fuel. After the combustion aid is added, the materials are evenly mixed by a high-speed stirring equipment, and the mixing time is controlled to 5-10 minutes to ensure the uniformity of the combustion aid in the material and avoid local excessive addition that affects the combustion performance and molding effect.

[0065] S5: Gradual pressing

[0066] The material after adding the combustion-supporting component is sent to the graded pressing and molding equipment, and the molding is completed according to the following steps:

[0067] The first stage: low-pressure pre-compression, pressure is 5-8MPa, temperature is 50-80℃;

[0068] The second stage: high pressure molding, with a pressure of 10-15MPa and a temperature of 150-200℃, to increase the density of the fuel block;

[0069] The third stage: cooling and shaping, the pressure is maintained at 8-10MPa, and the temperature drops to room temperature;

[0070] The final density of the fuel block reaches 1.2-1.4g / cm 3 , with high strength and high calorific value characteristics.

[0071] It should be noted that the material after adding the combustion aid described in this embodiment is evenly fed into the graded pressing and molding equipment through a quantitative conveying device to ensure that the pressure and temperature conditions of each batch of materials are consistent. Low pressure and low temperature are used in the first stage of pre-compression. By preliminarily removing residual air and increasing the contact area between particles, the foundation is laid for subsequent high-pressure molding. In the second stage of high-pressure molding, a multi-stage pressurization method is used to gradually increase the pressure and temperature, increase the material density and improve the uniformity of the internal structure through thermoplastic rheology. In the third stage of cooling and molding, a forced cooling system is equipped to control the cooling rate to avoid cracking of the fuel block due to excessive temperature difference between the inside and the outside, and optimize the mechanical strength and surface flatness of the molded block while maintaining pressure.

[0072] S6: Surface strengthening treatment

[0073] The surface of the fuel block is protected by using a mixed coating technology of plant wax and nano-alumina. The coating thickness is 50-100 nanometers. After coating, the fuel block has excellent moisture-proof and antioxidant properties, and the storage time can be extended to more than 12 months.

[0074] It should be noted that the vegetable wax and nano-alumina described in this embodiment are mixed in a mass ratio of 95:5, and prepared into a uniform coating liquid by a high-speed emulsifying device to ensure the stability and dispersibility of the coating liquid. The coating process adopts an automated spraying equipment, and a multi-angle nozzle is used for covering spraying. At the same time, the coating thickness is controlled within the range of 50-100 nanometers and the uniformity of the surface coating of the fuel block is ensured. After spraying, the surface of the fuel block is quickly solidified by a low-temperature hot air drying system to form a stable protective film of the coating, while improving its durability and adhesion. The moisture absorption rate of the coated fuel block is reduced by 30%-50% in the moisture resistance test, and the antioxidant capacity is increased by 20%-30% in the oxidation performance test, which significantly improves the safety and reliability of storage and transportation.

[0075] For S6: The experimental data of surface strengthening treatment are as follows

[0076] 1. Sample preparation

[0077] Control group: fuel blocks without coating treatment.

[0078] Experimental group: fuel blocks coated with a 50-100 nanometer thick mixed coating of vegetable wax and nano-alumina (coating ratio of 95:5, mass ratio).

[0079] 2. Test items

[0080] Moisture resistance test: The moisture absorption rate of the fuel block is measured in a high humidity environment (relative humidity 90%, temperature 25°C).

[0081] Antioxidation test: The fuel blocks were exposed to air (relative humidity 50%, temperature 25°C), and the calorific value changes and surface oxidation degree were tested every month.

[0082] Long-term storage stability test: Under normal storage conditions (relative humidity 50%, temperature 25°C), the appearance, density and calorific value changes of the fuel blocks were tested.

[0083] 3. Experimental data

[0084] a. Moisture-proof performance test data such as Figure 2 Shown

[0085] Results: The moisture absorption rate of the coated fuel blocks was reduced by about 70%, proving that the coating significantly improved moisture resistance.

[0086] b. Antioxidant capacity test data such as Figure 3 Shown

[0087] Results: The calorific value change of the coated fuel block was significantly slowed down, the oxidation rate was reduced by about 75%, and the performance remained more stable during long-term storage.

[0088] c. Long-term storage stability test data such as Figure 4 Shown

[0089] Results: After 12 months of storage, the surface crack rate of the coated fuel blocks decreased by 82%, the density change rate decreased by 73%, and the storage stability was significantly enhanced.

[0090] Conclusion: After coating with the mixed coating of vegetable wax and nano-alumina, the moisture absorption rate of the fuel block is reduced by 70%, the calorific value oxidation rate is reduced by 75%, and the surface crack rate and density change rate are significantly reduced during long-term storage. Under actual storage conditions, the coated fuel block can be stably stored for more than 12 months with good performance. The experimental data proves the effectiveness and excellence of this coating technology.

[0091] S7: Testing and Packaging

[0092] The finished fuel blocks are subjected to comprehensive quality inspection. The calorific value must reach 20-22MJ / kg, the compressive strength must reach above 2.5MPa, and the moisture content must not exceed 10%. Qualified fuel blocks are packaged using environmentally friendly and degradable materials, and the packaging is vacuum sealed to extend the storage time.

[0093] It should be noted that the finished fuel blocks described in this embodiment are quality tested batch by batch using a calorific value analyzer, a hydraulic strength tester and an infrared moisture meter to ensure that the calorific value, compressive strength and moisture content meet the standards, and the test data are recorded to ensure traceability. A biodegradable composite material with polylactic acid (PLA) and polybutylene succinate (PBAT) as the main components is used for packaging, and a vacuum sealing process is combined to effectively reduce the performance degradation of the fuel blocks due to oxidation and moisture absorption during transportation and storage.

[0094] The following is a detailed data description combined with the experimental steps:

[0095] 1. The purpose of the experiment is to verify whether the fuel blocks prepared by processes such as humidity adjustment, high-temperature physical modification, gas phase activation, addition of combustion-supporting components, graded pressing and molding, and surface strengthening treatment are superior to the existing technology in terms of calorific value, compressive strength, moisture resistance, antioxidant properties, and storage stability, so as to solve the problems of low fuel quality, difficult storage, and poor combustion performance in the background technology.

[0096] 2. Experimental materials and equipment, raw materials: urban domestic waste (kitchen waste, garden waste, paper and a small amount of plastic, etc.).

[0097] Equipment: drum screening equipment, air selection equipment, screw compression device, air flow activation device, grading press, automatic spraying machine; testing instruments: calorific value analyzer, hydraulic strength tester, infrared moisture meter, oxidation stability tester, moisture absorption rate tester.

[0098] 3. Experimental process

[0099] a. Humidity adjustment and pretreatment: 5 tons of mixed urban garbage are separated from fine ash and large impurities by drum screen, and then plastic, metal and glass are removed by air separation equipment. Low-temperature steam is used to adjust the humidity of the garbage at 50°C for 10 minutes, and the moisture content is finally uniformly controlled at 30%.

[0100] b. High-temperature physical modification: the humidity-adjusted garbage is sent to a screw compression device with the temperature controlled at 180°C and a compression ratio of 3:1. It is run continuously for 30 minutes. The released volatile organic compounds are recovered through a condensation collection device. The gaseous part is used for device heating and the liquid part is used for industrial utilization.

[0101] c. Carbon-based activation modification: the physically modified material is sent to the airflow activation device, using a mixed gas of oxygen and nitrogen (oxygen accounts for 7%), the temperature is controlled at 100°C, the pressure is maintained at 0.3MPa, and the processing time is 40 minutes.

[0102] d. Adding the combustion-supporting components: add the combustion-supporting agent (60% potassium nitrate, 30% magnesium carbonate, 10% nano-silicon dioxide) evenly to the activated material at a ratio of 5%, and run it through a high-speed mixing device for 5 minutes to ensure that the combustion-supporting agent is evenly distributed.

[0103] e. Grading pressing and molding, the material enters the grading pressing equipment:

[0104] The first stage: pressure 7MPa, temperature 70℃, pre-compression for 5 minutes;

[0105] The second stage: pressure 12MPa, temperature 170℃, pressing for 10 minutes;

[0106] The third stage: Cool to room temperature, maintain the pressure at 9MPa, and set for 5 minutes.

[0107] The final density is 1.3g / cm 3 High density fuel blocks.

[0108] f. Surface strengthening treatment, using plant wax and nano-aluminum oxide mixed coating technology, the coating thickness is controlled at 80 nanometers, and after spraying, it is cured by hot air to form a protective layer.

[0109] g. Finished product testing: testing the calorific value, compressive strength, moisture content, moisture resistance, antioxidant properties and storage stability of the fuel blocks.

[0110] Experimental data

[0111] 1. Fuel performance test data such as Figure 5 Shown

[0112] 2. Moisture-proof performance

[0113] The moisture absorption rate of the fuel block was tested in a high humidity environment (relative humidity 90%, temperature 25°C) as follows: Figure 6 As shown:

[0114] Results: The moisture absorption rate of the experimental group was reduced by about 75%, and the moisture-proof performance was significantly improved.

[0115] 3. Antioxidant Properties

[0116] The fuel blocks were stored in a natural environment (relative humidity 50%, temperature 25°C), and the data on the decrease in calorific value were as follows: Figure 7 As shown:

[0117] Results: The oxidation rate of the experimental group was reduced by about 78%, and the calorific value was more stable during long-term storage.

[0118] 4. Storage stability

[0119] After 12 months of storage, the appearance and density of the fuel blocks were tested. Figure 8 As shown:

[0120] Results: The surface crack rate of the experimental group decreased by 80%, and the density change rate decreased by 85%.

[0121] Technical Effects

[0122] Improve calorific value and combustion performance: The calorific value of the fuel block in the experimental group reaches 21.5MJ / kg, which is more than 20% higher than the existing technology. At the same time, the addition of combustion aids significantly improves the ignition performance and combustion stability.

[0123] Improved storage stability: The moisture absorption rate of the coated fuel block is reduced by 75%, and the oxidation rate is reduced by 78%. It can maintain excellent performance within 12 months, solving the problem of easy moisture absorption and oxidation of fuel blocks in the prior art.

[0124] Improved mechanical strength: The compressive strength of the finished fuel block reaches 2.8MPa, which is 1.9 times that of the existing technology, ensuring that it is not easily damaged during transportation and storage.

[0125] Specifically, drum screens and air separation technology are used to preliminarily remove impurities and improve material purity. Humidity adjustment further optimizes material uniformity. The fuel quality is insufficient, and the fiber modification effect is improved through high-temperature physical modification and carbon-based activation. The optimized design of the combustion aid further improves the fuel calorific value and combustion performance. The storage stability is poor, and surface strengthening treatment significantly improves moisture resistance and antioxidant properties. Coating technology and vacuum packaging extend the storage period of the fuel.

[0126] Specifically, first, impurities are separated and humidity is adjusted through drum screens and air separation equipment to make the material homogenized and the moisture content stabilized. Subsequently, high-temperature physical modification is used to destroy the cross-linking structure of cellulose and lignin, thereby improving the plasticity of the material. Gas phase activation is used to further increase the activity of carbon-based substances in the material and reduce the ash content. After adding a combustion aid, a high-density fuel block is obtained through multi-stage pressing and molding technology. Finally, the surface is strengthened by vegetable wax and nano-alumina coating to improve the moisture-proof and antioxidant properties of the fuel block, and vacuum packaging is used to extend the storage life. This technical solution effectively solves the problems of low sorting accuracy, insufficient fuel calorific value and density, and poor storage stability in the background technology, and significantly improves the efficiency of waste resource utilization and the industrial application value of biomass fuel.

[0127] In one embodiment of the present invention, Figure 1-Figure 8 As shown, in the humidity adjustment step, low-temperature steam acts on the garbage surface through multi-point injection, the steam temperature is 50-70°C, and the steam injection time is 5-10 minutes; the humidity adjustment process is equipped with a temperature and humidity sensor to ensure that the moisture content is within the range of 25%-35%, and the injection intensity and time are adjusted in real time to adapt to garbage with different humidity.

[0128] It should be noted that, in the embodiment described, the steam nozzles cover the garbage surface in an evenly distributed array through a multi-point injection method, and use an adjustable injection angle technology to ensure that the steam penetrates evenly into garbage of different shapes and densities. The equipped temperature and humidity sensors monitor the humidity changes inside and on the surface of the garbage in real time, and dynamically adjust the steam injection time, intensity and temperature in combination with the intelligent control system to ensure that the humidity adjustment process is stable and adapts to the complex composition changes of the garbage.

[0129] In one embodiment of the present invention, Figure 1-Figure 8 As shown, in the high-temperature physical modification step, a spiral compression device is used to gradually heat the garbage material to 150-200°C, and the heating rate is controlled at 10-20°C / minute to prevent excessive fiber decomposition caused by too fast heating. The compression ratio of the spiral compression device is 3:1, and it is equipped with a high-temperature corrosion-resistant coating to prevent volatile acidic substances from corroding the equipment during the treatment process. The volatile organic compounds (such as methane and ethanol) released during the treatment process are recovered through a condensation device and can be used for circulating heating or other industrial uses. The volatile gas recovery rate reaches more than 80%.

[0130] It should be noted that a segmented heating structure is arranged inside the spiral compression device described in this embodiment, and the temperature distribution of different heating areas is accurately adjusted through a multi-stage temperature control system to ensure that the material is heated evenly and avoid local overheating. At the same time, the condensing device adopts a multi-stage condensation recovery technology to separate the released volatile organic compounds into gaseous and liquid components, wherein the gaseous part is used for self-circulating heating of the device, and the liquid part is used for storage or other industrial purposes, thereby improving resource utilization and reducing environmental emissions.

[0131] In one embodiment of the present invention, Figure 1-Figure 8 As shown, in the carbon-based activation modification step:

[0132] The mixing ratio of oxygen and nitrogen in the gas phase activation device is 5%-10% oxygen and 90%-95% nitrogen;

[0133] The activation process lasts for 30-60 minutes, the pressure in the activation environment is controlled at 0.2-0.5MPa, and the gas flow rate is 5-10L / min;

[0134] After activation, the proportion of carbon-based active substances in the material increases by 10%-15%, and the ash content decreases to less than 3%.

[0135] It should be noted that the gas phase activation device described in this embodiment adopts a multi-layer gas distribution plate design, which ensures that the material surface is fully in contact with the gas by evenly distributing the airflow, thereby further improving the activation efficiency. During the activation process, an online monitoring system is equipped to detect the gas flow rate, pressure and material activation state in real time, and dynamically adjust the oxygen concentration and processing time according to the monitoring data to ensure that the generation of carbon-based active substances is optimized while effectively reducing the ash content.

[0136] In one embodiment of the present invention, Figure 1-Figure 8 As shown, the inorganic nanoparticles in the combustion-supporting component are nano-silicon dioxide with a particle size range of 10-50 nanometers. The total addition ratio of the combustion-supporting agent is 5%-8% of the material weight. It is fully mixed with the material through high-frequency vibration mixing technology to ensure the uniform distribution of the combustion-supporting component in the fuel block. The graded pressing and molding equipment is a multi-axis multi-stage pressing machine. The compression channel in the equipment is designed in sections. The initial pressure channel length is 30%-40%, and the high-pressure channel length is 50%-60%. A high-temperature resistant and wear-resistant coating is set in the channel to extend the life of the equipment. In the surface strengthening treatment step, the plant wax is beeswax, palm wax or candelilla wax, the particle size of nano-alumina is 50-100 nanometers, and the addition ratio is 3%-5% of the total weight of the plant wax. The coating process adopts spraying + hot melt technology, and the coating thickness is controlled at 50-100 nanometers, the surface smoothness error is controlled within ±5 nanometers, the moisture absorption rate of the coated fuel block is reduced by 30%-50%, and the moisture-proof effect can be maintained for more than 12 months. The calorific value detection in the detection step uses an automatic combustion calorimeter, and the detection error is controlled within ±1%; the compressive strength detection uses a high-precision hydraulic tester, and the detection error is controlled within ±0.1MPa; the moisture content detection uses an infrared moisture analyzer, the detection range is 0.1%-20%, and the detection error is less than ±0.5%. The packaging material is prepared by mixing polylactic acid (PLA) and polybutylene succinate (PBAT) in a mass ratio of 70:30, and adding 2%-5% of plant fiber reinforcement material. The packaging material has good mechanical strength and degradability, and the packaging thickness is controlled at 30-50 microns.

[0137] It should be noted that the nano-silicon dioxide combustion-supporting component described in this embodiment is pre-dispersed and then mixed in layers with the material in a high-frequency vibration mixing equipment to ensure uniform particle distribution and enhance the bonding force between the combustion aid and the matrix. A segmented pressure sensing system is used in the multi-axis multi-stage pressing machine to monitor the pressure changes in the compression channel in real time, optimize the molding effects in the initial pressure and high-pressure stages, and reduce the wear of the equipment during operation through the self-lubricating properties of the high-temperature and wear-resistant coating. The mixed coating of vegetable wax and nano-alumina is treated with an ultrasonic homogenizer to improve the stability and adhesion of the coating. During the spraying process, an infrared hot melt device is combined to ensure that the coating cures quickly and has a consistent thickness. In the hygroscopic performance test, the coated fuel block has a 30%-50% reduction in moisture absorption rate within 12 months, and the coating integrity remains good during storage, while significantly reducing surface cracks and performance attenuation. The plant fiber reinforcement components in the packaging material are refined to improve the tensile strength and toughness of the packaging, and are sealed in a low-pressure environment through vacuum packaging equipment to extend the storage time of the fuel block and the environmental protection performance maintenance cycle.

[0138] In summary, the method for producing biomass molded fuel from urban domestic waste in the embodiment of the present invention utilizes processes such as humidity regulation, high-temperature physical modification, gas phase activation, addition of combustion-supporting components, multi-stage pressing and molding, and surface strengthening treatment to achieve efficient resource utilization of waste. First, through the combination of drum screen and air separation equipment, large impurities and irregular inorganic matter in the garbage are preliminarily removed, and low-temperature steam is used to adjust the humidity of the garbage, controlling the moisture content at 25%-35% to ensure the uniformity and stability of material processing; then the humidity-adjusted garbage is sent to the spiral compression device to destroy the cross-linking structure of cellulose and lignin under high temperature and high pressure environment of 150-200℃, and the released volatile organic matter is recovered through the condensation device to improve resource utilization efficiency; then through the gas phase activation process, the mixed gas of oxygen and nitrogen is used to further increase the proportion of carbon-based active substances in the material under low temperature and slightly positive pressure conditions, while reducing the ash content; on this basis, a combustion aid composed of nano-silicon dioxide, potassium nitrate and magnesium carbonate is evenly added to the activated material, and the high-frequency vibration mixing technology is used to ensure the uniform distribution of the combustion aid in the material, improve the combustion performance and fuel stability; then the material enters the graded pressing and molding equipment, and undergoes three stages of low-pressure pre-compression, high-pressure molding and cooling and shaping in sequence, and finally obtains a density of 1.2-1.4g / cm 3high-strength fuel blocks; finally, the surface of the fuel block is sprayed with a mixed coating technology of plant wax and nano-alumina and formed into a coating by hot melt curing. The coating thickness is controlled within the range of 50-100 nanometers, which significantly improves the moisture resistance and antioxidant capacity of the fuel block. At the same time, the environmentally friendly and degradable packaging materials and vacuum sealing process are combined to effectively extend the storage period of the fuel block and maintain stable performance. This technical solution solves the problem of low precision in waste treatment and sorting in the background technology, and improves the purity and molding performance of the material through methods such as humidity regulation and high-temperature modification; at the same time, the optimization of the combustion aid and the gas phase activation process significantly improve the calorific value, density and combustion stability of the fuel, overcoming the problems of low calorific value and high ash content of the fuel in the prior art; in addition, the combination of coating treatment and vacuum packaging greatly improves the storage stability and moisture resistance and antioxidant properties of the fuel block, effectively solving the defects of the prior art that the fuel is easy to absorb moisture, easy to oxidize, and not resistant to storage, and significantly improves the overall efficiency of waste resource utilization and the industrial application value of fuel.

[0139] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention.

Claims

1. A method for producing biomass briquette fuel from municipal solid waste, characterized in that: The following steps are involved: S1: Humidity regulation and pretreatment The municipal solid waste is separated by a drum screen combined with an air separation device to remove large or irregular impurities, including plastic, metal and glass. Low-temperature steam is used to adjust the humidity of the waste to a uniform moisture content of 25%-35% to optimize the efficiency and consistency of subsequent processing technology; S2: High temperature physical modification The humidity-adjusted garbage is put into a screw compression device to physically modify the garbage under a temperature of 150-200°C and a high pressure environment to destroy the cross-linking structure of cellulose and lignin, improve the plasticity and uniformity of the material, and the volatile organic matter generated during the treatment process is recovered through a condensation collection device for circulating heating or industrial use; S3: Carbon-based activation modification The incompletely decomposed part of the material surface is subjected to gas phase activation treatment by an airflow activation device, using a 5%-10% oxygen and nitrogen mixed gas, maintaining a low temperature (80-120°C) and slightly positive pressure (0.1-0.5MPa) environment to generate carbon-based active substances with high combustion performance. The gas-phase activated material has higher combustion efficiency and lower ash content; S4: Addition of combustion-supporting components Adding a modified combustion aid to the garbage material after gas phase activation treatment, the combustion aid is composed of potassium nitrate, magnesium carbonate and inorganic nanoparticles, wherein potassium nitrate accounts for 60%-70% of the total weight, magnesium carbonate accounts for 20%-30%, and inorganic nanoparticles account for 5%-10%. The combustion aid can improve the ignition performance and combustion stability of the fuel and reduce the generation of combustion ash; S5: Gradual pressing The material after adding the combustion-supporting component is sent to the graded pressing and molding equipment, and the molding is completed according to the following steps: The first stage: low-pressure pre-compression, pressure is 5-8MPa, temperature is 50-80℃; The second stage: high pressure molding, with a pressure of 10-15MPa and a temperature of 150-200℃, to increase the density of the fuel block; The third stage: cooling and shaping, the pressure is maintained at 8-10MPa, and the temperature drops to room temperature; The final density of the fuel block reaches 1.2-1.4g / cm 3 , with high strength and high calorific value characteristics; S6: Surface strengthening treatment The surface of the fuel block is protected by using a mixed coating technology of plant wax and nano-alumina. The coating thickness is 50-100 nanometers. After coating, the fuel block has excellent moisture resistance and antioxidant capacity, and the storage time can be extended to more than 12 months. S7: Testing and Packaging The finished fuel blocks are subjected to comprehensive quality inspection. The calorific value must reach 20-22MJ / kg, the compressive strength must reach above 2.5MPa, and the moisture content must not exceed 10%. Qualified fuel blocks are packaged using environmentally friendly and degradable materials, and the packaging is vacuum sealed to extend the storage time.

2. The method for producing biomass briquette fuel from municipal solid waste according to claim 1, characterized in that: In the humidity adjustment step, low-temperature steam acts on the garbage surface through multi-point injection, the steam temperature is 50-70°C, and the steam injection time is 5-10 minutes; the humidity adjustment process is equipped with a temperature and humidity sensor to ensure that the moisture content is within the range of 25%-35%, and the injection intensity and time are adjusted in real time to adapt to garbage with different humidity.

3. The method for producing biomass briquette fuel from urban domestic waste according to claim 1, characterized in that: In the high-temperature physical modification step, a spiral compression device is used to gradually heat the waste material to 150-200°C, and the heating rate is controlled at 10-20°C / minute to prevent excessive fiber decomposition caused by too fast heating. The compression ratio of the spiral compression device is 3:1, and it is equipped with a high-temperature corrosion-resistant coating to prevent volatile acidic substances from corroding the equipment during the treatment process. The volatile organic matter (such as methane and ethanol) released during the treatment process is recovered through a condensation device and can be used for circulating heating or other industrial uses. The volatile gas recovery rate reaches more than 80%.

4. The method for producing biomass briquette fuel from municipal solid waste according to claim 1, characterized in that: In the carbon-based activation modification step: The mixing ratio of oxygen and nitrogen in the gas phase activation device is 5%-10% oxygen and 90%-95% nitrogen; The activation process lasts for 30-60 minutes, the pressure in the activation environment is controlled at 0.2-0.5MPa, and the gas flow rate is 5-10L / min; After activation, the proportion of carbon-based active substances in the material increases by 10%-15%, and the ash content decreases to less than 3%.

5. The method for producing biomass briquette fuel from municipal solid waste according to claim 1, characterized in that: The inorganic nanoparticles in the combustion-supporting component are nano-silicon dioxide with a particle size range of 10-50 nanometers. The total addition ratio of the combustion-supporting agent is 5%-8% of the material weight. It is fully mixed with the material through high-frequency vibration mixing technology to ensure uniform distribution of the combustion-supporting component in the fuel block.

6. The method for producing biomass briquette fuel from municipal solid waste according to claim 1, characterized in that: The graded pressing and forming equipment is a multi-axis multi-stage pressing machine. The compression channel in the equipment is designed in sections. The length of the initial pressure channel is 30%-40%, and the length of the high-pressure channel is 50%-60%. A high-temperature and wear-resistant coating is set in the channel to extend the life of the equipment.

7. The method for producing biomass briquette fuel from municipal solid waste according to claim 1, characterized in that: In the surface strengthening treatment step: The vegetable wax is beeswax, palm wax or candelilla wax, the particle size of nano-alumina is 50-100 nanometers, and the addition ratio is 3%-5% of the total weight of the vegetable wax; The coating process adopts spraying + hot melt technology, the coating thickness is controlled at 50-100 nanometers, and the surface smoothness error is controlled at ±5 nanometers; The moisture absorption rate of the coated fuel block is reduced by 30%-50%, and the moisture-proof effect can be maintained for more than 12 months.

8. The method for producing biomass briquette fuel from municipal solid waste according to claim 1, characterized in that: The calorific value test in the detection step uses an automatic combustion calorimeter, and the detection error is controlled within ±1%; the compressive strength test uses a high-precision hydraulic tester, and the detection error is controlled within ±0.1MPa; the moisture content test uses an infrared moisture analyzer, with a detection range of 0.1%-20% and a detection error of less than ±0.5%.

9. The method for producing biomass briquette fuel from municipal solid waste according to claim 1, characterized in that: The packaging material is prepared by mixing polylactic acid (PLA) and polybutylene succinate (PBAT) in a mass ratio of 70:30, and adding 2%-5% of plant fiber reinforcement material. The packaging material has good mechanical strength and degradability, and the packaging thickness is controlled at 30-50 microns.

Citation Information

Cited By

  • Biomass derived fuel based on other garbage and preparation method thereof

    CN122012152A